2010
DOI: 10.1152/ajpregu.00320.2010
|View full text |Cite
|
Sign up to set email alerts
|

The water-absorption region of ventral skin of several semiterrestrial and aquatic anuran amphibians identified by aquaporins

Abstract: Regions of specialization for water absorption across the skin of Bufonid and Ranid anurans were identified by immunohistochemistry and Western blot analysis, using antibodies raised against arginine vasotocin (AVT)-stimulated aquaporins (AQPs) that are specific to absorbing regions of Hyla japonica. In Bufo marinus, labeling for Hyla urinary bladder-type AQP (AQP-h2), which is also localized in the urinary bladder, occurred in the ventral surface of the hindlimb, pelvic, and pectoral regions. AQP-h2 was not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
(63 reference statements)
2
23
0
1
Order By: Relevance
“…These observations also confirmed that canonical AQP2 is not encoded in the genome of the Western-clawed frog [24] or its congener the African clawed frog. The Bayesian analyes show that the wholly aquatic Western-clawed frog has two paralogs of AQP5 , a canonical form ( AQP5 , formerly annotated as AQP-x5 , [28]) and a related paralog ( AQP5L , formerly annotated as AQP2 ) encoded between two AQP6 genes, the urinary bladder-type ( AQP6ub ) and the ventral skin type ( AQP6vs ) formerly identified as (h2-like and h3-like) type-a2 anuran specific aquaporins [23], [24], [32]. Amongst other Anura the Bayesian data provide statistical support for three paralogs of AQP6 (see Table S2), the urinary bladder type ( AQP6ub ) and two paralogs ( AQP6vs1 , -6vs2 ) that mediate cutaneous hydration through the ventral skin of semi-aquatic and semi-terrestrial anurans [33], [35].…”
Section: Resultsmentioning
confidence: 99%
“…These observations also confirmed that canonical AQP2 is not encoded in the genome of the Western-clawed frog [24] or its congener the African clawed frog. The Bayesian analyes show that the wholly aquatic Western-clawed frog has two paralogs of AQP5 , a canonical form ( AQP5 , formerly annotated as AQP-x5 , [28]) and a related paralog ( AQP5L , formerly annotated as AQP2 ) encoded between two AQP6 genes, the urinary bladder-type ( AQP6ub ) and the ventral skin type ( AQP6vs ) formerly identified as (h2-like and h3-like) type-a2 anuran specific aquaporins [23], [24], [32]. Amongst other Anura the Bayesian data provide statistical support for three paralogs of AQP6 (see Table S2), the urinary bladder type ( AQP6ub ) and two paralogs ( AQP6vs1 , -6vs2 ) that mediate cutaneous hydration through the ventral skin of semi-aquatic and semi-terrestrial anurans [33], [35].…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence that skin thickness is associated with habitat aridity at the species level (Toledo and Jared 1993), with species from drier areas producing a thicker epidermis which reduces dehydration rates whilst also impeding water uptake. Further, aquaporins (water channel proteins) embedded within the pelvic patch (Kubota et al 2006) can influence rehydration rates in anurans, and variation in the density and type of aquaporins among species has been interpreted as an adaptation of frogs to their respective hydric environment (Suzuki et al 2007;Ogushi et al 2010). It is currently unknown whether similar patterns of morphological or physiological differences in the skin properties exist at the population level, and we encourage future studies to explore the underlying mechanisms that drive intraspecific differences in dehydration and rehydration rates across hydric gradients.…”
Section: Dehydration and Rehydration Rates In Adult Malesmentioning
confidence: 99%
“…In Bufo sp . the inguinal area has the highest capacity for transcutaneus absorption (Ogushi et al. 2010), so the volume of water used to induce the animals was enough to submerge a third of their height.…”
Section: Methodsmentioning
confidence: 99%
“…In Bufo sp. the inguinal area has the highest capacity for transcutaneus absorption (Ogushi et al 2010), so the volume of water used to induce the animals was enough to submerge a third of their height. Furthermore maintaining the animals in a low volume of water facilitated the introduction of a sponge or a piece of fabric to the container enabling the head to be kept clear of the water once the righting reflex was abolished.…”
Section: Animal Subjectsmentioning
confidence: 99%